The Plural Marker ‘’ of English & ‘’ of Limbu : Comparison based on Pronunciation - Lawati, Hari Chandra (Journal of Nepalese Studies, 2025)
This paper examines the pronunciation of the plural marker <-s> pronounced by the Yakthung/Limbu-speaking English learners. Drawing on a qualitative research design (Taylor, 2016), the study is based on data collected from twenty Grade 8 students at Phidim Secondary School, where English- and Nepali-medium classes are conducted in parallel. In addition, three English teachers participated in the study. As noted by Dirsa and Andika (2022), teachers’ practices significantly shape learning outcomes, as they serve as facilitators, mentors, and evaluators in the classroom. The findings indicate that linguistic diversity and instances of overgeneralization (Baihaqi, 2020) pose challenges for learners’ pronunciation of plural forms; however, these difficulties can be addressed through creative and targeted instructional strategies. The study highlights the need for both teachers and learners to be aware of pronunciation issues during the teaching–learning process.